Assessment of design procedures for structural glass beams - Crompton, P; P. R. Crompton (1999)
In structural design, ductile materials are usually preferred, because failure is rarely sudden and catastrophic. Once the material has yielded, large observable strains will occur before total collapse of a structure. This thesis is about the structural use of glass. Glass is probably the most perfectly brittle material that exists. It demonstrates linear elastic behaviour right up to the point of failure. When a piece of glass fails, this always happens suddenly, by the high-speed propagation of a crack through the entire element. If glass is so different from the most common primary structural materials namely steel and reinforced concrete, then should we be using the same basic design approach for both? This thesis reviews current design methods tracing their development through this century. Current code formers are keen to bring all materials under the umbrella of Limit State Design. This philosophy has been developed for ductile materials and is shown to be somewhat inappropriate for materials where the main design criterion is not ultimate strength. A further chapter looks as the statistical behaviour of multi-ply beams. This was highlighted, at the recent Glass in Buildings conference, as being an important area for further research. It has been shown that statistically two or more beams are always better than one of equivalent thickness. A method of reducing the thickness of a glass beam, without affecting its probability of failure, has been described. This could have significant cost implications in the design of glass beams. It should be noted that this thesis is not about face-loaded glass elements such as windowpanes or structural glazing, where designs are governed by deflection and generally executed using rules of thumb, but about edge-loaded elements where strength governs and more rigorous design rules are required.